1997
DOI: 10.1002/(sici)1099-0720(199704)11:2<95::aid-acp429>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Earwitness Testimony: Never Mind the Variety, Hear the Length

Abstract: Three aspects of voice recognition were investigated in the study reported here: memory for familiar voices, memory for the words spoken, and the relative effects of length and variation in a voice extract on long‐ and short‐term memory. In Experiment 1, recognition memory for the briefly heard voice of a stranger was superior with longer extracts (p<0.01), but increasing vowel variety did not improve performance. This pattern was repeated for short‐term memory (p<0.01) in Experiment 2. Scores for the above ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 14 publications
(25 reference statements)
2
16
0
Order By: Relevance
“…Research on identifications independent of facial identifications has generally focused on using voice or body characteristics as identifiers, with varying degrees of success (Cook & Wilding, 1997;Philippon, Cherryman, Bull, & Vrij, 2006;Pryke et al, 2004). Accuracy in identifying a voice sample is dependent on a number of factors, including familiarity of the speaker's voice, length of exposure to the voice and number of voice foils in the line-up (Cook & Wilding, 1997). Most research has therefore found it to be difficult for witnesses to accurately identify a suspect through their voice (Cook & Wilding, 1997;Olsson, Juslin, & Winman, 1998).…”
Section: Types Of Identificationsupporting
confidence: 65%
See 2 more Smart Citations
“…Research on identifications independent of facial identifications has generally focused on using voice or body characteristics as identifiers, with varying degrees of success (Cook & Wilding, 1997;Philippon, Cherryman, Bull, & Vrij, 2006;Pryke et al, 2004). Accuracy in identifying a voice sample is dependent on a number of factors, including familiarity of the speaker's voice, length of exposure to the voice and number of voice foils in the line-up (Cook & Wilding, 1997). Most research has therefore found it to be difficult for witnesses to accurately identify a suspect through their voice (Cook & Wilding, 1997;Olsson, Juslin, & Winman, 1998).…”
Section: Types Of Identificationsupporting
confidence: 65%
“…Accuracy in identifying a voice sample is dependent on a number of factors, including familiarity of the speaker's voice, length of exposure to the voice and number of voice foils in the line-up (Cook & Wilding, 1997). Most research has therefore found it to be difficult for witnesses to accurately identify a suspect through their voice (Cook & Wilding, 1997;Olsson, Juslin, & Winman, 1998).…”
Section: Types Of Identificationmentioning
confidence: 78%
See 1 more Smart Citation
“…These favourable conditions included short delay, long exposure to the target voice during encoding, with the speech samples for the events lasting between 45 and 50 seconds. This was well above the duration necessary for optimum voice identification (Cook & Wilding, 1997;Pollack, Pickett, & Sumby, 1954).…”
Section: Methodsmentioning
confidence: 99%
“…We have only found a handful of empirical studies concerned with children's voice-memory. Some of them have limited relevance in the present context since they are concerned with memory for familiar voices (Bartholomeus 1973;Murry and Cort 1971;Spence et al 2002), and it is not possible to generalise findings about familiar voices to identification of unfamiliar voices (Cook and Wilding 1997;Van Lancker and Kreiman 1985).…”
Section: Previous Researchmentioning
confidence: 99%